Repentance Education: The Gate of Heaven That is Always Open A Community Outreach Program for The Congregation Of Al-Mukmin Mosque Pekanbaru - Wali Saputra (Indo Publishing, 2026)
This community service initiative aimed to deepen the spiritual understanding and awareness of the Al-Mukmin Mosque congregation in Pekanbaru regarding the Islamic concept of tawbah (repentance). The program was conceived in response to a discernible pattern of moral decline and spiritual disorientation among contemporary Muslim communities, compounded by the underutilization of the mosque as a center for community development and religious formation. Titled